HMGB1 contributes to osteoarthritis of temporomandibular joint by inducing synovial angiogenesis. (9th December 2020) - Feng, Yaping; Hu, Shiyu; Liu, Li; Ke, Jin; Long, Xing
Abstract: Background: High‐ mobility group 1 protein (HMGB1) is related with inflammation. Our former research reported that substantial HMGB1 situates at the synovium of osteoarthritis of temporomandibular joint (TMJOA) patients. Objective: This study investigated whether HMGB1 promotes synovial angiogenesis of TMJOA and its underlying mechanism. Methods: Human synovial fibroblasts were stimulated with HMGB1; the expression of vascular endothelial growth factor (VEGF) and hypoxia‐inducible transcription factor‐1α (HIF‐1α) in these cells was explored by Western blotting, real‐time PCR and immunofluorescent staining. The angiogenic capacity of these cells was assayed by tube formation and cell migration of human umbilical vein endothelial cells (HUVECs). The specific inhibitor against HMGB1, VEGF, Erk or JNK was added in these cells, respectively. Complete Freund's adjuvant (CFA)‐induced TMJOA rats were produced. The changes in their synovium and synovial fluid were detected by immunofluorescent staining and ELISA. Results: HMGB1 effectively up‐regulated the production of VEGF and HIF‐1α in TMJOA synovial fibroblasts through the activation of Erk and JNK. Conditioned medium from HMGB1‐treated TMJOA synovial fibroblasts significantly promoted tube formation and migration in HUVECs, while attenuated those after the addition of certain inhibitor for VEGF. Furthermore, the specific inhibitor against HMGB1 vanished the neovascularisation and production of HIF‐1α, VEGF and CD34 in the synovium of rat TMJOA induced by CFA injection. Additionally, this inhibitor led to the reduction of IL‐6, IL‐1β and TNF‐α in the synovial fluid of those rats. Conclusion: These findings disclose a key role for HMGB1 in governing synovial angiogenesis and as a therapeutic target against TMJOA.